Percutaneous endoscopic gastrostomy placement in paediatric Crohn's disease patients contributes to both improved nutrition and growth. (8th March 2018) - Duncan, H; Painesi, A; Buchanan, E; McGrogan, P; Gerasimidis, K; Walker, G; Haddock, G; Russell, RK
Abstract: Aim: This paper describes the outcomes of gastrostomy feeding in patients with Crohn's disease (CD). Methods: Patients with CD who attended the Royal Hospital for Children, Glasgow and received gastrostomy feeding for at least two years between 2003 and 2010 were identified from the clinical database. The data recorded included the anthropometric data, CD phenotype, the surgical technique that was used, complications, medication, feed type, median feed, calories, volume and clinical outcomes. Results: The study identified 16 patients (14 male) who had a gastrostomy inserted using a pull technique at a median age of 12.6 years. Of these two required laparoscopic placement. Short‐term complications lasting less than one month were experienced by nine (56%) patients and one (6%) experienced long‐term complications. Anthropometry significantly improved at follow‐up compared to baseline: at 12 months, the body mass index z‐score was 1.11 (p = 0.005) and the weight z‐score was 0.19 (p < 0.05). At 24 months, the height z‐score was ‐1.03 (p = 0.04). The daily median volume and calories from feeds increased significantly from baseline to post‐PEG insertion, from 400 to 738 mL and 705 to 860 kcal/day (p ≤ 0.01). Conclusion: Gastrostomy feeding for paediatric patients with CD was associated with improved nutrition, weight gain and growth outcomes.